Ottoman passports anti-anarchism, security, and controlling geographical mobility (1876-1908) - Yılmaz, İlkay 1981- (Modern Intellectual and Political History of the Middle East, 2023)
Yilmaz_Ottoman Passports-cvr to au -- Yilmaz Final.